2005
DOI: 10.1081/ja-200048464
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Like a Guy: Frequent Binge Drinking Among Undergraduate Women

Abstract: The purpose of this exploratory study was to examine why there has been an increase in frequent binge drinking among the most recent generation of female undergraduate students. Specifically, we examined whether female undergraduate women associated being able to "drink like a guy" (e.g., drink large amounts of alcohol, drinking competitively) with gender equality. Focus groups were conducted in March of 2003 with 42 female undergraduate women who consumed alcohol. Participants were recruited from respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
168
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(186 citation statements)
references
References 20 publications
14
168
1
3
Order By: Relevance
“…This suggests that if one were to find two heavy drinking samples of young adults who were identical on everything except their sex, the women would tend to binge more over time than men. More recent studies from college studies have documented increased binge drinking among young women -as a badge of honor to be able to drink "like a guy" as well as to receive positive attention from male peers (Young et al, 2005). In our case, this finding may also be a function of this particular sample-women in the stage of emerging adulthood who already are problem drinkers.…”
Section: Discussionsupporting
confidence: 49%
“…This suggests that if one were to find two heavy drinking samples of young adults who were identical on everything except their sex, the women would tend to binge more over time than men. More recent studies from college studies have documented increased binge drinking among young women -as a badge of honor to be able to drink "like a guy" as well as to receive positive attention from male peers (Young et al, 2005). In our case, this finding may also be a function of this particular sample-women in the stage of emerging adulthood who already are problem drinkers.…”
Section: Discussionsupporting
confidence: 49%
“…Prior research has shown that adolescents who are more susceptible to peer pressure have more difficulty establishing social competence and have a harder time making their own judgments about risk-taking behaviors (Allen et al 2006). Similarly, Young et al (2009) qualitative study found that college females described their drinking patterns as motivated by pressure to make favorable impressions on their male peers. As such, it is important to identify factors that contribute to certain youth's heightened vulnerability to peer pressure.…”
Section: Who Are More Resistant To Deviant Peer Pressure: Males or Fementioning
confidence: 83%
“…A growing body of work has begun to establish the predictive power of susceptibility to deviant peer influence on adolescents' risk-taking behaviors, a determinant of behavior that appears to be a general risk factor across genders. Building on the burgeoning research showing adolescents are highly attuned to picking up on and responding to social cues from their environments (Blakemore and Mills 2014), we examine whether and how deviant peer influence affects adolescent males and females differently during a period of development in which gender stereotypes may be especially influential in shaping perceived social norms (de Visser and McDonnell 2011;Young et al 2009). …”
Section: The Present Studymentioning
confidence: 99%
“…Women may view alcohol as a means of facilitating communication and sexual expression, including initiating a relationship, finding intimacy, or coping with the loss or failure of an existing relationship (Gleason, 1994a(Gleason, , 1994b. In turn, women may be placing themselves at higher risk for sexual assault (Young et al, 2005); in fact, over 50% of all sexual assaults on college campuses involve alcohol (Abbey, 2002). Thus, physiological differences, increases in drinking among women, and the increased risk attached to the first year of college underscore the need for interventions targeted to 1st-year women.…”
mentioning
confidence: 99%